Model Manajemen kelompok Usaha Mikro Kecil dan Menengah (UMKM) Usaha Tepung Tapioka - Salahudin, Salahudin; Wahyudi, Wahyudi; Ulum, Ihyaul; Kurniawan, Yudi (ARISTO, 2018)
Micro Small and Medium Enterprises (MSMEs) is a buffer of the national economy that it proved able to survive during the monetary crisis in Indonesia in 1997-1998. On the one hand, MSMEs have a strong resilience to the economic crisis. On the other hand, the development of MSMEs is faced with complex problems. This research departs from the complexity of the problems faced in developing Tapioca Starch business. This study aims to understand the problems faced by SMEs in developing Tapioca Flour Business in Kediri and prepare concrete steps to solve the problem. This research used descriptive qualitative method with data collection technique of interview, observation, and documentation. The results of this study indicated that the problems faced by the Tapioca flour business in Kediri are that they have no the formation of the business in a business group, the lack of human resources skills in developing the business, the limited business capital, and the dependence of the entrepreneurs on the middlemen directly and not to the detriment of entrepreneurs. The steps proposed for such issues include the formation of business groups, strengthening cooperative networks with business groups, markets, and cassava growers, and strengthening venture capital through saving and loan systems.